Analisis pelaksanaan marking pra bedah Di rsud arifin achmad pekanbaru - Riraname - Siregar; Wasisto - Utomo; Misrawati - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Marking is marking an area of ​​a surgery which is intentionally to identify an incision area. This activity is related to the safety of the patients, that aims to prevent the wrong side, wrong procedure, and wrong patient on the surgical implementation. This research was targeted to analyze the implementation of the pre- surgical marking in accordance with Standard Operating Procedures (SOPs) of any hospitals that also refer to the International Standard Accreditation (Joint Commission International). This research applied a simple descriptive design. There were 134 samples taken by a total sampling technique. Observation sheets were used as instruments of measurements. Analysis applied was univariate analysis. Of 134 respondents used as targets of marking implementation, 131 respondents were found on the target in the pairing area, 1 respondent on multiple lesions, and 2 respondents on multiple structures. The results showed: of 134 respondents, 131 respondents (74.9 %) were not marked with the marking technique, but pre- surgical markings were performed on 33 respondents/patients (25.1 %). From the analysis performed on the 33 patients there were no implementations of pre- surgical marking conducted in accordance with the SOPs of the hospital. Therefore, the result of this study has indicated there have still been many markings performed, nevertheless some markings have not been executed in accordance with the SOPs. The result of this research study is expected that all related health workers, doctors and nurses are to improve the implementation of the marking nurses for the future so that patient safety in the operating room may be improved. Keywords : marking , patient safety